Uji Aktivitas Antidiabetes Ekstrak Etanol Daun Sintrong (Crassocephalum crepidioides (Benth.) S. Moore) Terhadap Tikus Putih Jantan Yang Diinduksi Aloksan - Muharni Saputri; Debi Sanura Boru perangin angin; Salmah Handayani Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Diabetes is a disease that occurs over a long period of time caused by the pancreas not being able to produce insulin optimally or the body not using insulin effectively. The administration of antidiabetic drugs in the form of insulin and oral is the treatment for diabetes. However, because the price is expensive for the middle to lower class, the treatment of sintrong leaf medicinal plants (Crasocephalum crepidioides (Benth.) S. Moore m mm) was developed. The purpose of this study was to determine the effectiveness of ethanol extract of sintrong leaves as an antidiabetic and able to reduce blood sugar levels (BSL) from fasting male white rats induced by alloxan. Methods; The stages of this study include plant identification, preparation of dry powder simplisia, characterization of simplisia, screening of secondary metabolite compounds (phytochemistry), extraction of dry simplisia powder of sintrong leaves, and testing of antidiabetic activity using 25 rats divided into 5 groups, the negative control group (CMC-Na), the positive control group (metformin), the test group of ethanol extract of sintrong leaves at a dose of 75 mg / kgbw, 150 mg / kgbw, and 300 mg / kgbw. As a test group, the administration of extracts to rats was given orally and then the BSL was measured. Blood sugar was determined at the beginning of fasting, day 3, 6, 9, 12, 15. Blood sugar of each group was statistically analyzed by one-way ANOVA method. Results; Based on the test results from each test group, the ethanol extract of sintrong leaves showed that the ethanol extract of sintrong leaves as antidiabetic activity that can reduce fasting BSL in male rats with an effective dose of 150 mg/kgbb with BSL obtained 89.40 mg/dL on day 15